Improving efficiency for removal of ammoniacal nitrogen from wastewaters using hydrodynamic cavitation - Patil, Pravin B.; Bhandari, Vinay M.; Ranade, Vivek V. (Ultrasonics Sonochemistry, 2021)
The present study reports significant improvements in the removal of ammoniacal nitrogen from wastewater which is an important problem for many industries such as dyes and pigment, distilleries and fisheries. Pilot plant studies (capacity, 1 m(3)/h) on synthetic wastewater using 4-amino phenol as model nitrogen containing organic compound and two real industrial effluents of high ammoniacal nitrogen content were carried out using hydrodynamic cavitation. Two reactor geometries were evaluated for increased efficiency in removal-orifice and vortex diode. Effect of initial concentration (100-500 mg/L), effect of pressure drop (0.5-5 bar) and nature of cavitating device (linear and vortex flow for cavitation) were evaluated along with effect of salt content, effect of hydrogen peroxide addition and aeration. Initial concentration was found to have significant impact on the extent of removal: similar to 5 g/m(3) removal for initial concentration of 100 mg/L and up to 12 g/m(3) removal at high concentration of 500 mg/L. Interestingly, significant improvement of the order of magnitude (up to 8 times) in removal of ammoniacal nitrogen could be obtained by sparging air or oxygen in hydrodynamic cavitation and a very high removal of above 80% could be achieved. The removal of ammoniacal nitrogen by vortex diode was also found to be effective in the industrial wastewaters and results on two different effluent samples of distillery industry indicated up to 75% removal, though with longer time of treatment compared to that of synthetic wastewater. The developed methodology of hydrodynamic cavitation technology with aeration and vortex diode as a cavitating device was found to be highly effective for improving the efficiency of the conventional cavitation methods and hence can be highly useful in industrial wastewater treatment, specifically for the removal of ammoniacal nitrogen.
Keywords: Amino phenol; Cavitation; Oxidation; pollution; Wastewater treatment

Wastewater treatment and process intensification for degradation of solvents using hydrodynamic cavitation - Patil, Pravin B.; Bhandari, Vinay M.; Ranade, Vivek V. (Chemical Engineering and Processing-Process Intensification, 2021)
Industrial wastewater treatment for removal of small concentrations of harmful solvents is pertinent issue in many chemical and pharmaceutical industries. The present work evaluates removal of three common solvents by hydrodynamic cavitation (nominal capacity, 1m(3)/h). Solvent degradation of three solvents viz. octanol, dimethyl formamide and cyclohexanol was studied in the concentration range of 50-200 mg/L and for the pressure drop range of 0.5-5 bar. The vortex based cavitation device (vortex diode) was compared with that of linear flow based device (orifice). Process intensification in the form of aeration and addition oxidizing agent-hydrogen peroxide was also evaluated for synergistic effect. The vortex diode required lower pressure drop and is superior to orifice and process intensification using aeration is most effective. A reduction in TOC to the extent of 74% could be achieved for octanol (200 ppm) using aeration with cavitational yield of 1202x10(-4) mg/J for vortex diode, yield similar to 10 times of orifice. The degradation depends on the nature of solvent and it was revealed that low values of dielectric constant (epsilon<10) favour degradation. The kinetics was evaluated using rate model based on per-pass degradation factor. The process techno-economic feasibility is useful in industrial wastewater treatment.
Keywords: Cavitation; Effluent; Organics removal; Oxidation; pollution